Floristic Study and Species Diverisy of Msallata-Garaboulli Province in Libya - Abdurrazag S. Sherif; Mohammed H. Mahklouf; Abdalla G. Betelmal (Britain International of Exact Sciences (BIoEx) Journal, 2020)
A survey of plant species of Msallata and Garaboulli was taken in between 2017-2018. A total number of 468 different plant taxa have been collected from the study area representing 68 families of which 57 families and 389 species are belonging to dicotyledons, 8 families and 76 species belonging to monocotyledons, and 3 families with one species each belonging to Gymnosperms. The results of this study shows that the dominance of the family Asteraceae with 78 species followed by the family Fabaceae with 59 species, the family Poaceae with 47 species, Brassicaceae with 27 species and Apiaceaew with 19 species. Other families such as Liliaceae, Caryophylaceae, Lamiaceae, Cistaceae, Boraginaceae, Plantaginaceae, and Rubiaceae were represented by 16, 15, 14, 13, 12, 10, 10 species respectively. The result have also shown that the gerera Plantago, and Silene are the most sizable genera with 10, 8 species respectively. Lifeform spectrum analysis have shown the predominance of therophytes with 231 species, followed by Hemicryptophytes with 62 species, while chorotype spectrum analysis have shown the dominance of Mediterranian species, followed by Mediterrean/Iranu-Turanean species.